The extension teacher in the Division of Tarlac a descriptive profile - Dacayanan, Emiliano F. 1928- (s.n.], 1969)
This is a descriptive profile of extension teachers in the Division of Tarlac made due to the absence of meaningful information about this particular sector of the personnel of the Department of Education.